BURNS: WHERE ARE WE STANDING WITH PROPRANOLOL, OXANDROLONE, rhGH, AND THE NEW INCRETIN ANALOGUES? - Gauglitz, Gerd G (2011)
PURPOSE OF REVIEW: The hypermetabolic response in critically ill patients is characterized by hyperdynamic circulatory, physiologic, catabolic and immune system responses. Failure to satisfy overwhelming energy and protein requirements after, and during critical illness, results in multiorgan dysfunction, increased susceptibility to infection, and death. Attenuation of the hypermetabolic response by various pharmacologic modalities is emerging as an essential component of the management of severe burn patients. This review focuses on the more recent advances in therapeutic strategies to attenuate the hypermetabolic response and its associated insulin resistance post-burn. RECENT FINDINGS: At present, beta-adrenergic blockade with propranolol represents probably the most efficacious anti-catabolic therapy in the treatment of burns. Other pharmacological strategies include growth hormone, insulin-like growth factor, oxandrolone and intensive insulin therapy. SUMMARY: Novel approaches to the management of critical illness by judicious glucose control and the use of pharmacologic modulators to the hypercatabolic response to critical illness have emerged. Investigation of alternative strategies, including the use of metformin, glucagon-like-peptide-1 and the PPAR-γ agonists are under current investigation.